PENGEMBANGAN BUKU DIGITAL FLIPBOOK PELAJARAN BAHASA INDONESIA KELAS IV SDN 41 PONTIANAK UTARA - Kusumasadi, Dimas Kuncoro; Kresnadi, Hery; Ghasya, Dyoty Auliya Vilda (Universitas Tanjungpura, 2025)
This research generally aims to develop digital books using the canva application assisted by flipbook made for Indonesian language lessons in class IV SDN 41 North Pontianak, which are valid, practical, and attractive to support student learning. This study employs a research methodology that incorporates Research and Development (RnD) alongside the ADDIE model. The data for this research was collected from a single class consisting of 26 students in the fourth grade at SDN 41 North Pontianak. Validator I validator II is a media and material expert. Data were collected through observation, interviews, and questionnaires. The findings from the study indicated that the process of creating digital books utilizing the Canva application, supplemented by Flipbook, in Indonesian language instruction for fourth-grade students, successfully progressed through four of the five stages of the ADDIE model. The validation of the product developed through this method achieved a percentage score of 89% by combining the results of data from validator I and validator II and fall into the